Zooming out of the crisis: Language and human collaboration - Guillén, Gabriel; Sawin, Thor; Avineri, Netta (Foreign language annals, 2020)
Language teachers are often masters of using the physical space in their language classrooms, rearranging furniture, groups, and artifacts to facilitate meaningful encounters with and among learners. Indeed, during the COVID‐19 crisis, many language teachers are sharing that these human encounters—reading learners' needs through body language, moving in and out of conversations, or engaging each other face‐to‐face—are the biggest felt loss in their emergent digital language classrooms. Yet, the new digital realities do not necessarily mean that teachers must sacrifice real collaboration among their learners. Digital tools were often designed to explicitly facilitate multimodal collaboration, and, with a wider variety of humans and human stories than may be found within the four walls of the typical classroom. This article aims to help language teachers facilitate more diverse interactions in the target language through the use of tools, spaces, and strategies that can be easily incorporated into our digital classrooms. We describe three categories of such activities (mobile‐assisted learning, tandem learning, and service‐learning) and explain how these can be most effectively incorporated into an online language class. The Challenge Videoconferencing tools such as Zoom are being widely used as an immediate response to remote language teaching needs. However, these tools are rarely ideal as a replacement for the classroom's physically embodied engagement. What alternatives exist for educators facilitating students' language growth and human collaboration?